Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 7. Beitrag. Diptera: Asilidae. - Moucha, Josef; Hradský, Milan (Contributions to Entomology = Beiträge zur Entomologie, 1963)
The above publication deals with the authors’ results on the faunistic exploration of the family Asilidae (Diptera) of Albania. During the expedition of the Deutsches Entomologisches Institut there were collected 226 specimens of this family belonging to 33 species and 1 forma. 23 species have proved new to the fauna of Albania.